Multicultural Islamic Education in the Fatwa of the Indonesian Ulema Council on Digital Da'wah Ethics - Widoyo, Agus Fatuh; Zulihi, Zulihi; Islamy, Athoillah; Abduh, Muhammad (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Exclusive, intolerant, and radical da'wah content on various social media platforms is a challenge for Islamic da'wah in today's digital era. This qualitative study through a normative-philosophical approach aims to identify and explore the dimensions of multicultural Islamic education values in the fatwa of the Indonesian Ulema Council of East Java Province Number. 06 of 2022 concerning Da'wah Ethics in the Digital Era. The theory of multicultural Islamic education conceptualized by Azyumardi Azra becomes the theory of analysis of the subject matter of this study. Data analysis through reduction, presentation, and verification. This study shows the content of multicultural Islamic education values in legal provisions related to da'wah ethics in the dital room in the fatwa of the Indonesian Ulema Council of East Java Province, including the value of humanism education in the prohibition of the delivery of da'wah content that spreads hatred and insults even for the reason of amar makruf nahi munkar. Then, the value of tasamuh education in the recommendation of delivering pluralist da'wah content, which is able to respect Islamic beliefs that are still being debated. Furthermore, the value of peace education in advocating the delivery of nationalist da'wah content. Next, the value of wasatiyah education in recommending the delivery of da'wah content that maintains public conduciveness and stability. The theoretical implications of this study affirm that the mainstreaming of multicultural Islamic educational values can be internalized through religious social fatwas in Indonesia, as well as fatwas related to da'wah ethics in the digital space.